POSTPARTUM PERFORMANCE AS INFLUENCED BY BODY WEIGHT CHANGES AT PARTURITION IN BUFFALOES
Twenty normal parturient Murrah buffaloes were divided into 2 groups of 10 each depending upon their body weight loss at parturition compared to the one week prepartum, i.e. Group I (G I) lost more than 10% while Group II (G II